A comparative analysis of serum albumin from different species to determine a natural source of albumin that might be useful for human therapy. Issue 3 (June 2016) - Nurdiansyah, Rizky; Rifa'i, Muhaimin; Widodo
الملخص: أهداف البحث: يعتبر زلال الدم أحد أكثر البروتينات انتشارا في البلازما البشرية، ويقوم بوظائف في نقل البروتين، والتخلص من الشوارد الحرة، وتنظيم الضغط الأسموزي. أُستخدم زلال الدم في العلاج البشري في حالات عديدة منها نقص الدم، ونقص الزلال في الدم وأمراض الكبد المزمنة. إلا أن التطبيقات الطبية للزلال تبقى غير واضحة، خاصة في ما يتعلق بالإصابات الفيروسية واختيار المتبرع المناسب. ويُعتبر بديل زلال الدم البشري من مصدر طبيعي آخر بديلا قابلا للاستخدام. لذا درسنا صفات التشابه، والعلاقات البنيوية والتطويرية لزلال الدم لسبع فصائل مختلفة. طرق البحث: قمنا بمقارنة ترتيب وبنية وخصائص زلال الدم من عدة أنواع من المخلوقات باستخدام أسلوب "إن - سيليكو" التحليلي فقط. النتائج: تشير المعلومات إلى أن لزلال الدم مجموعات تسلسل متعددة الأشكال ومرتبة، مبنية على الأنواع المتشابهة. إلا أن تعدد الأشكال لا يغير البنية ثلاثية الأبعاد المسئولة عن وظيفتها كناقل. ويمتلك زلال "دجاج الأدغال الأحمر" العدد الأقل من المواصفات الجزيئية التي تشبه إلى حد كبير جزيء زلال الدم البشري. الاستنتاجات: تُعتبر هذه الدراسة محورية في توفير معلومات واضحة عن زلال أنواع أخرى من الكائنات المشابه في بنيته مع زلال الدم البشري. قد يتم استخدام هذه الأنواع الأخرى من الزلال كمصدر أساسي طبيعي لعلاج البشر. Abstract: Objectives: Serum albumin (SA) is one of the most abundant proteins in human plasma and performs functions for protein transport, scavenges for free radicals, and regulates osmotic pressure. SA has been used for therapy in humans with several diseases including hypovolemia, hypoalbuminemia, and chronic liver disease. However, the most appropriate source of albumin for medical applications remains unclear, especially in the case of viral infections, which complicates finding viable donors. Substitution of human serum albumin (HSA) with albumin from other natural sources is a viable alternative. Therefore, we elucidated the similarity in character, structure and evolutionary relationship among serum albumin isolated from seven different species. Methods: We compared the sequence, structure, and properties of SA from different species using an in-silico approach. Results: These data suggested that SA has sequence polymorphism that clusters based on closely related-species. However, these polymorphisms do not change the three-dimensional structure of the protein; this may serve to maintain its function as a transporter. The Gallus gallus albumin has the lowest number of the epitopes that closely resemble HSA. Conclusion: This study is crucial in providing explicit information about the structural similarity of albumin isolated from other species compared to HSA. The Gallus gallus SA might be used as a primary natural source of albumin where warranted for human therapy.